Hypertension prevalence and control among community‐dwelling lebanese older adults. Issue 9 (9th August 2020) - Fakhri, Ghina; Assaad, Sarah; Chaaya, Monique
Abstract: There is a high prevalence of hypertension among Lebanese adults, but no evidence is available on its prevalence and control exclusively among older adults (65 + years). This study provides the first evidence on a representative sample of 502 community elderly and presents the basis for future research and policy implications. Results show an overall prevalence of 52% with a significantly higher female‐to‐male ratio. Factors independently associated with hypertension were older age, body mass index, and dementia. More than a third of those with a positive history of hypertension had uncontrolled blood levels. Uncontrolled hypertension was higher among women. Increasing awareness about medication adherence and controlling multi‐morbidities constitute promising measures to lowering the burden of hypertension among Lebanese older adults, especially women.